A `glue sniffer` teenager with anuric renal failure and hepatitis - Yurtseven, Ali; Türksoylu, Mümine; Yazıcı, Pınar; Karapınar, Bülent; Saz, Eylem Ulaş (The Turkish Journal of Pediatrics, 2018)
`Inhalant abuse` is a common form of volatile drug abuse throughout the world especially in developing countries. This substance mainly contains toluene. Acute toluene inhalation produces a biphasic response with an initial central nervous system (CNS) excitation followed by CNS depression as well as various metabolic alterations. Chronic inhalational abuse is associated with muscular weakness, gastrointestinal symptoms, renal and hepatic injury. In this report, a 16-year-old boy presented with jaundice, nausea, vomiting and reduced urine output. He developed severe acute renal/hepatic damage due to abuse of gas products. Since toluene is the main toxic agent involved in glue sniffing which is metabolized to hippuric acid, the present case was treated with continuous hemodiafiltration, plasma exchange and conservative therapy to eliminate hippuric acid. The jaundice gradually disappeared, he had complete recovery of renal/hepatic functions in ten days. We aimed to increase the awareness among emergency physicians that ``glue sniffing` should be considered in the differential diagnosis of unexplained reversible acute renal/hepatic damage.